2015
DOI: 10.2174/1568026615666150302105622
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeable Lipophilic Cations as Mitochondrial Directing Groups

Abstract: The mitochondrion's negatively charged membrane potential has been well documented to drive the accumulation of membrane permeable delocalized lipophilic cations (DLC). DLC attachments to known bioactive compounds can direct organelle localization and improve drug exposure to targets within the mitochondria. Due to the mitochondria's essential function and its regulation of cell death, DLC targeted therapies are the focus of drug discovery projects altering cellular fate via mitochondrial targets. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…Notably, following their pretreatment with DLC-carboranes, only normal cells were seen to recapitulate their full proliferation potential in media that were free from these compounds; this effect was verified through dilution assays. The selective effect of the functionized carboranes appears to be linked to their DLC moiety, which elicits a cytotoxic response with a therapeutic potential through mitochondrial targets [11,18], since: a) triphenylphosphonium ions (TPPs), have been exploited as small molecule directing groups to achieve mitochondrial delivery [17]; b) rhodamine functionalities have been utilized in mitochondria-specific dyes [11,15,20]; and, c) dequalinium (DQA) has been evaluated in a therapeutic approach for the treatment of B-cell chronic lymphocytic leukemia (B-CLL), acute promyelocytic leukemia (APL) and hepatocellular carcinoma (HCC) [32,33]. [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, following their pretreatment with DLC-carboranes, only normal cells were seen to recapitulate their full proliferation potential in media that were free from these compounds; this effect was verified through dilution assays. The selective effect of the functionized carboranes appears to be linked to their DLC moiety, which elicits a cytotoxic response with a therapeutic potential through mitochondrial targets [11,18], since: a) triphenylphosphonium ions (TPPs), have been exploited as small molecule directing groups to achieve mitochondrial delivery [17]; b) rhodamine functionalities have been utilized in mitochondria-specific dyes [11,15,20]; and, c) dequalinium (DQA) has been evaluated in a therapeutic approach for the treatment of B-cell chronic lymphocytic leukemia (B-CLL), acute promyelocytic leukemia (APL) and hepatocellular carcinoma (HCC) [32,33]. [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that as long as technological advancements empower the translational medicine capacity in enabling the pharmacological exploitation of cancer cell molecular and genomic knowledge, the advances to therapeutically overcome heterogeneity and to target the tumor cell microenvironment will occur at increasing rates [2][3][4][5][6][7][8][9][10]. A major milestone towards organelle-specific drug delivery was reached by the discovery of delocalized lipophilic cations (DLCs) [11]. These molecular structures are guided selectively towards tumors by the higher mitochondrial transmembrane potential (~60 mV difference) that is consequent to the correspondingly higher metabolic activity of cancer cells relative to that of normal cells [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all cationic compounds are MDR-recognizable and, with highly lipophilic analogs, the positive charge becomes less important for recognition and the subsequent effluxing mechanism by MDR [73]. Studies also suggest that cancer cell phenotypes that do not express MDR and have greater mitochondrial membrane potential are more likely to be sensitive to delocalized lipophilic cations and mitochondria-targeted cationic agents [74], [75].…”
Section: Targeting Mitochondrial Metabolism: Selective Accumulation Omentioning
confidence: 99%
“…20) He proposed that π-delocalized lipophilic cations (DLCs) could penetrate the hydrophobic barriers of the plasma and mitochondria membrane under a cross-membrane negative potential. [21][22][23] The mitochondrial membrane potentials of carcinoma cells are more negative than those of normal cells, and this negative membrane charge induces the selective transfer of DLCs into carcinoma mitochondria. If DLCs are toxic to mitochondria at high concentrations, their selective accumulation in carcinoma mitochondria should induce selective carcinoma cell killing.…”
Section: π-Delocalized Lipophilic Cationic Motifmentioning
confidence: 99%